A millimeter wave broadband wireless access technology demonstratorfor the next generation Internet network reach extension. - Izadpanah, H. (IEEE Communications magazine)
We report design and implementation scenarios for a gigabit-capacity and high-data-rate fixed wireless access technology demonstrator. The system is based on a broadband wireless access concept and implementation techniques utilizing millimeter-wave and newly introduced free-space optical wireless high-speed links. The demonstration platform is to provide broadband ?last mile? access and networking solutions to Internet users in densely populated areas with homes and businesses (e.g., building-centric and inner city environments) in need of high bandwidth not served by the fiber infrastructure. The investigation focuses on the radio link design, network architecture, system integration, and a compatible interface to the existing ATM fiber and satellite core networks in support of the next-generation Internet (NGI) reach network extension by the wireless technology